Analysis of the process of raising the temperature in the spark channel at a discharge in gas - Korytchenko, K.V.; Volkolupov, Yu.Ya.; Krasnogolovets, M.A.; Ostrizhnoy, M.A.; Chumakov, V.I.; Semenets, T.A. (Вопросы атомной науки и техники, 2001)
Analysis of the process of raising the temperature in the spark channel at a discharge in gas is performed. The quantitative evaluation was made in main for the air. The effect of steadying a thermodynamic equilibrium in gas, as well as the influence of power discharge parameters on the process of temperature increasing was analyzed. The quantitative evaluation of time parameters of the processes of rotary, oscillatory relaxation, dissociation and ionization has allowed to reveal the influence of each of them on temperature increasing in the spark channel. The problems arising in the course of practical realization of a spark discharge which influence on the process of temperature raising are detected, and the ways for their solution are determined. The results obtained can be put in a basis of developing the methods to design devices for intensive increase of temperatures in gas media using the electrical discharge, as well as for analysis of a dependence of shock wave intensity on dynamic parameters of the electrical discharge.